A Hybrid Intelligent Model for Humanities Education: Integrating Multi-Agent Systems, Cognitive Computing, and NLP to Foster Independent Learning - Mohamed Badawi Elkhalifa (The Indonesian Journal of Computer Science, 2026)
This study aims to design an intelligent e-learning system that integrates cognitive computing, multi-agent systems, expert systems, and natural language processing (NLP) techniques within a single unified platform. The system’s architecture is grounded in the independent learner model, which serves as the overarching pedagogical framework that organizes and regulates all its components. The researcher employed an experimental approach using a pretest-posttest design with two equivalent groups. The sample consisted of 50 male and female students from the College of Arts and Islamic Studies at Wasl University in Dubai. Participants were equally and randomly assigned to either an experimental group that received instruction through the proposed system or a control group that continued learning through conventional methods. Results of the independent-samples t-test revealed statistically significant differences at the (p < 0.001) level in favor of the experimental group across all three measured programming skills. The average effect size reached d = 2.71 according to Cohen’s coefficient, indicating a very large effect.